2021
DOI: 10.3390/ijerph182413384
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Exercise on Mental Health: From Cognitive Improvements to Risk of Addiction

Abstract: (1) Background: we aimed to investigate the effects of physical activity on cognitive functions and deficits of healthy population and other needy groups. Secondly, we investigated the relation between healthy habits and psychopathological risks. Finally, we investigated the impact of COVID-19 pandemic on exercise addiction and possible associated disorders. (2) Methods: From April 2021 to October 2021, we conducted a review aimed at identifying the effects of physical exercise on mental health, from cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Consistent with numerous studies on the benefits of physical exercise [ 2 , 11 ], our findings indicated that physical exercise was positively associated with undergraduate students’ adaptation and subjective well-being. It is well-established that regular physical exercise and exercise habits are indispensable components of a healthy lifestyle that bring great benefits to physical and psychological health and adaptation [ 9 , 12 , 42 ]. Particularly, physical exercise also contributes to people’s psychological health and social adaptation [ 2 ], and the good physical condition brought about by exercise also contributes directly to social adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with numerous studies on the benefits of physical exercise [ 2 , 11 ], our findings indicated that physical exercise was positively associated with undergraduate students’ adaptation and subjective well-being. It is well-established that regular physical exercise and exercise habits are indispensable components of a healthy lifestyle that bring great benefits to physical and psychological health and adaptation [ 9 , 12 , 42 ]. Particularly, physical exercise also contributes to people’s psychological health and social adaptation [ 2 ], and the good physical condition brought about by exercise also contributes directly to social adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise refers to body movements made by skeletal muscles via the expenditure of energy. There are many health and adaptation benefits associated with physical exercise; specifically, regular physical exercise can promote both physical health (e.g., physiological function, such as vital capacity and strength, ideal body fat percentage, and body mass index) and psychological adaptation [ 9 , 10 ]. Several studies have shown that physical exercise has a negative relationship with perceived stress, depression, anxiety, suicide attempts, and even suicidal behavior but a positive relationship with self-esteem, self-efficacy, psychological capital, and life satisfaction [ 1 , 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, neuroticism, as with other personal and situational parameters, could be an important factor underlying the difference between using exercise as a healthy or maladaptive coping strategy [92,94]. Similarly, Golshani et al found that mental toughness could moderate the association between heavy exercising and greater mental health issues in that lower mental toughness was associated with worse mental health issues among heavy exercisers [32].…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that physical exercise reduces impulsivity. Adherence to exercise (60 min of moderate-to-vigorous physical activity per day) enhanced the treatment and prevention of impulsivity-related disorders [ 80 ]; physical activity improved attention and executive functions and reduced hyperactivity and impulsivity in children with ADHD [ 81 ]. Among adolescents, less frequent vigorous physical activity was associated with greater negative urgency and lack of perseverance [ 82 ], and the amount and intensity of physical exercise per week were negatively correlated with emotion-related impulsivity levels [ 83 ].…”
Section: Discussionmentioning
confidence: 99%